O ensino de arte e a educação inclusiva: Um estudo de caso com os professores na rede municipal de Cabedelo - PB - Alves, Marines Salviano (2016)
This case study arose from the need to understand how the teacher of Visual Arts develops its inclusive teaching practices with students with disabilities enrolled in public schools in Cabedelo - PB. Aiming to investigate whether there are difficulties reported by teachers of Visual Arts and, consequently, how the practices of inclusive education of these educators are being held in the municipal schools of elementary school. The empirical field was determined by Board of Inclusive Education (BIE), Arts Coordination and two municipal schools in Cabedelo - PB that have Multifunctional Resource Room (MRR). Data from this study were obtained through direct observation, application of semi-structured questionnaires, with managers and Visual Arts teachers of the selected schools; with the BIE and the Arts Coordination. The methodological phase of documentary research was conducted by analyzing the specific legislation for the area, such as the Declaration of Salamanca (1994), the Law of Guidelines and Bases of National Education (1996) and the very Brazilian Constitution (1988) to be official documents dealing with educational policies. The theoretical framework involved art field of knowledge, training of the teacher of Visual Arts and Inclusive Education, approaching authors as Morin (2011), Barbosa (2005), Costa (2010), Fonseca da Silva (2000, 2013), Coll et al (2004), Bauman (2000, 2013). The results show that teachers of Visual Arts started to become more involved with the content on the School Inclusion through the actions promoted by the Department of Education and Culture and the BIE; the teacher of Visual Arts does not get in their education, subsidies that makes it able to meet the demand of students in classes which are present students with various types of disabilities; SRM available in the surveyed schools are not standardized because there are significant differences that undermine the effectiveness of this pedagogical complementation. It is worth noting that these differences in SRM include the furniture and technological resources.